2015
DOI: 10.1002/hed.24065
|View full text |Cite
|
Sign up to set email alerts
|

Salvage surgery for locally recurrent oropharyngeal cancer

Abstract: Surgical salvage for oropharyngeal SCC after failure of radiotherapy (+/- chemotherapy) is feasible. Patients who may benefit from surgery include those without regional recurrence and/or those in whom negative margins can be obtained. However, patients may be tracheotomy or gastrostomy tube dependent. The p16 status did not seem to have prognostic impact in the salvage setting; however, larger series are required to assess this relationship. © 2015 Wiley Periodicals, Inc. Head Neck 38: E658-E664, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
86
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(104 citation statements)
references
References 33 publications
(77 reference statements)
10
86
0
8
Order By: Relevance
“…Salvage modality was another important prognostic factor associated with OS. Consistent with recent reports, surgical salvage conferred a significant prognostic advantage as compared to nonsurgical salvage (aHR = 0.45; 95% CI = 0.21–0.98) . It is important to underscore the potential for selection biases, such as comorbidities, performance status, and/or resectability of recurrence, which may have influenced the type of salvage therapy and survival outcomes.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Salvage modality was another important prognostic factor associated with OS. Consistent with recent reports, surgical salvage conferred a significant prognostic advantage as compared to nonsurgical salvage (aHR = 0.45; 95% CI = 0.21–0.98) . It is important to underscore the potential for selection biases, such as comorbidities, performance status, and/or resectability of recurrence, which may have influenced the type of salvage therapy and survival outcomes.…”
Section: Discussionsupporting
confidence: 73%
“…Conversely, positive margins may represent poor selection criteria for surgical therapy and/or an unfavorable tumor location. Multiple studies have shown that a positive surgical margin predicts a greater risk of recurrence after salvage, but only one previous study has investigated margin status in the setting of recurrent HPV‐oropharyngeal SCC …”
Section: Discussionmentioning
confidence: 99%
“…Guo et al [22] reported that surgical salvage was associated with improved OS for 65 cases of recurrent locoregional OPSCC and 43 cases of distant metastatic OPSCC; this relationship existed independently of tumour HPV status. This result is consistent with a study reported by Patel et al [23] in which HPV status was not associated with either OS or relapse-free survival in 34 patients who underwent salvage surgery for locally recurrent or persistent OPSCC after chemoradiotherapy. In the current study, because the majority of the salvage therapies did not consist of surgery but rather of chemoradiotherapy, the HPVpositive patients who underwent surgery as a first-line therapy for OPSCC had a survival advantage.…”
Section: Discussionsupporting
confidence: 83%
“…However, patients treated with salvage surgery may be tracheotomy or gastrostomy tube dependent. p16 status did not appear to have prognostic impact in the salvage setting [6]. …”
Section: Introductionmentioning
confidence: 99%
“…The overall survival (OS) rate of patients treated with re-irradiation at 2-year range from 30% to 67% according to RT techniques (external beam 3-dimensional RT versus intensity modulated RT versus high-dose-rate brachytherapy) and disease extension (outcome in resectable disease suitable for re-irradiation ranges from 30% to 48% while outcome with re-irradiation in non-resectable disease ranges from 5% to 20% at 2 years) [6-10]. …”
Section: Introductionmentioning
confidence: 99%